(untitled) (The Journal of Psychology and Sociology, 2023)
The article deals with the problem of diagnosing the level of formation of emotional intelligence of older preschool children. The author conducts such methods as "diagnostic technique of emotional identification" (E. I. Izotova), "behavior assessment" (T.B. Marcinkovskaya, M. Mitr) and a differentiated assessment of a child’s emotional intelligence during observation in order to identify the features of emo-tional intelligence of older preschool children and analyzes the results of a diagnostic study. The results of an empirical study showed that the level of development of emotional intelligence in older preschool children was medium and low. A program of correctional and developmental classes is being created and conducted, which shows a positive result. For the formation of the emotional intel-ligence of older preschool children, recommendations are given on the expression of various emotional states, the identification and understanding of the emotions of others, as well as the systematic conduct of specially organized classes on the development of facial expressions, the development of pantomime skills and expressiveness of movements, coherent speech. Key words: emotion, emotional intelligence, older preschool children, the level of development of emotional intelligence.